Renal Transplant Outcome in Children with an Augmented Bladder - Pereira, Pedro L.; Rodriguez, Ruben O.; Camblor, Carlota F.; Urrutia, María José M.; Romera, Roberto L.; Roman, Laura E.; Monereo, Enrique J. (Frontiers in Pediatrics, 2013)
Objective. Studies evaluateing renal transplant (RT) outcome in children who underwent an augmentation cystoplasty (AC) are contradictory and the current knowledge is based on studies with a limited number of patients. The aim of this study is to compare RT outcome between children who underwent AC and those without augmentation. Patients and methods. A total of 20 p who underwent an AC prior to the RT (12 with ureter and 8 with intestine) were enrolled in the study and were compared to a control group of 24p without AC, transplanted in the same time period (1991-2011). Data including; age at transplant, allograft source, urological complications, UTI incidence, the presence of VUR, and patient and graft survival were compared between the groups. Results. Mean age at RT and mean follow up were 9.7 vs 7.9 yrs and 6.9 vs 7.9 yrs in the AC group and control group, respectively (NS). The graft originated in living donors for 60% of AC patients and 41.6% of the control RT patients. The rate of UTI were 0.01 UTI /patient/ year and 0.004 UTI/patient/year in the augmented group and controls, respectively (p=0.0001). In the AC group of 14p with UTIs, 10 (71%) had VUR and 5p out of 8 (62.5%) in the control group had VUR. In the AC group, of the 7 p with > 3 UTIs, 3 (43%) were noncompliant with CIC and the incidence of UTIs was not related with the type of AC or if the patient did CIC through a Mitrofanoff conduit or through the urethra. Graft function at the end of study was 92.9±36.85 ml/min/m2 in the AC group and 88.17±28.2 ml/min/m2 in the control group (NS). Graft survival at 10 years was also similar 88% in the AC group and 84.8% in controls. In the AC group 3p lost their grafts and 5 in the control group with respective mean follow-up of 10.6 + 4.3 and 7.1+ 4.7 years. Conclusions. There are no significant differences in the RT outcome between children transplanted with AC or without. However, recurrent UTIs are more frequent in the former group and these UT